E-guidebook Automotive Tourism South West Java: A Special Guide For Solo Riding Pro-Environment - Arief, Aylin Yumna; Syahreza, Alfi; Susanto, Eko; Aldilama P, Mochammad Refael (Talenta Publisher, 2021)
This product is motivated by the growth of the productive age in Indonesia which encourages the development of a dynamic and innovative lifestyle. Work pressure experienced by people of productive age has made the life cycle of this age segment more varied on weekends or on holidays. This phenomenon then led to the activity of motorbike riding (solo riding) from the city where you live to explore tourism destinations in inland areas. so that it can become an information center that can make it easier for people to visit a destination and something that is needed by every city, region that manages tourism activities. The development of technology, especially information, has made the tourism business grow. There are various terms used as an information center, one of which is Eguidebook. Besides having a function as a center for information about tourism to tourists who come, it can also be used as a tourism promotion tool. In the area of ​​South West Java, there is still a lack of interest in tourists to visit this is due to a lack of information about routes, tourist attractions, accommodation, and other supporting facilities. The making of this project aims to create an electronic design document for solo riding activities to the South West Java Region which prioritizes the principles of sustainable tourism, the design is carried out by searching for information in the South West Java Region types of tourist information needs, visual compilation, prototyping, user evaluation and finalizing the design. It is hoped that this project can be useful for those interested in solo riding and people who like to do automotive tourism